Impact of destination weddings in tourism economy - Pereira, L.; Mendonça, S.; Dias, Á.; Lopes da Costa, R.; Gonçalves, R. (International Journal of Economics and Business Research, 2022)
Despite representing a recent world trend, wedding tourism felt a growth of 75% the past few years, which shows this market, specifically, the destination weddings niche, is proving to have an optimistic development and becoming a relevant topic in events tourism. The research objective analyses how the destination weddings have contributed for the development of events tourism in Portugal by examining what tactics are being utilised towards an international positioning. A quantitative method was used to achieve the objectives, being that two distinct surveys were elaborated, to foreign couples and another to vendors that take part in the industry. The data triangulation method was adopted with the goal of obtaining robust results by gathering a broader source of data. The results show that the destination weddings market contributes positively to the expansion of the events tourism in Portugal. Couples tend to choose Portugal for their climate, impressive sites and sense of intimacy, but the country needs to improve the transaction payments and present a wider range of advertisement. Regarding Covid-19, it had a negative influence mainly because most foreign couples decided to postpone or cancel the wedding.